Settlement approaches in the Italian Asylum System from the point of view of health professionals and social workers: SETTLEMENT APPROACHES IN THE IAS - Mancini, Tiziana; Bottura, Benedetta; Rossi, Michele (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: Medical and inclusion/exclusion settlement approaches are the two main approaches characterizing the reception practices into the Western host societies. These settlement approaches guide how professionals take care for forced migrants and favor or obstacle autonomy and integration of asylum seekers and refugees into host societies. Still, few studies have analysed how professionals perceive the settlement approaches that guide their work with forced migrants. This study aimed to analyse the representations that a sample of 256 Italian health professionals and social workers working in both governmental and non-governmental organisations had of the settlement approaches that guided their work in the Italian Asylum System (IAS). Methods: Semi-structured interviews were conducted and content and lexically analysed, focusing on the professionals’ perceptions of the critical issues in the access of forced migrants into the IAS services. Results: Professionals perceived four types of critical issues, making more often reference to organisational weakness than to legal-normative-procedural, relational, and professional weakness. Such critical issues linked to four different perceptions of settlement approaches –social exclusion, medical, relational, and organisational– that guided, sometimes simultaneously, the professionals’ practices depending on the work area, the institution/association in which they worked, and their role in the organisation. Conclusion and practical implications: Guiding the professionals’ work, settlement approaches could favor or obstacle autonomy and integration of asylum seekers and refugees into host societies. The results may inform policy and future services highlighting potential prospects for services oriented toward autonomy and integration of this growing population.